2012
DOI: 10.1111/j.1528-1167.2011.03395.x
|View full text |Cite
|
Sign up to set email alerts
|

Epilepsy in Tanzanian children: Association with perinatal events and other risk factors

Abstract: PurposeTo define the prevalence and risk factors for epilepsy in children in a rural district of Tanzania by conducting a community-based case–control study.MethodsChildren aged 6–14 years with active epilepsy (at least two unprovoked seizures in the last 5 years) were identified in a cross-sectional survey in Tanzania. Cases were compared with age-matched controls.Key FindingsOverall 112 children with epilepsy (CWE) were identified; the unadjusted prevalence of epilepsy was 2.91 per 1,000 (95% confidence inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
33
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 45 publications
8
33
0
Order By: Relevance
“…In general, a history of complications during the perinatal period was associated with epilepsy in this population. Similar findings have been noted in rural studies done within the region . This finding is potentially of public health importance because it points toward the need for ensuring a successful, closely monitored pregnancy period for Ugandan mothers and rigorous emergency and obstetric care for the mother‐baby pair.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In general, a history of complications during the perinatal period was associated with epilepsy in this population. Similar findings have been noted in rural studies done within the region . This finding is potentially of public health importance because it points toward the need for ensuring a successful, closely monitored pregnancy period for Ugandan mothers and rigorous emergency and obstetric care for the mother‐baby pair.…”
Section: Discussionsupporting
confidence: 81%
“…Adults were more likely to have epilepsy if they had a positive family history of seizures. The strong association of family history of seizures with epilepsy for both children and adults has consistently been noted in previous studies done in Africa as well as in other population studies, which noted a two‐ to fourfold increased risk of epilepsy among the first‐degree relatives of people with genetic epilepsies or epilepsies whose cause was unknown, compared with the general population.…”
Section: Discussionsupporting
confidence: 75%
“…Our study showed that those with a history of head injury and encephalitis were more likely to have persistent seizures in pregnancy; these aetiologies are commonly associated with seizure and epilepsy in Africa [7,41]. …”
Section: Discussionmentioning
confidence: 99%
“…Untreated adverse perinatal complications are associated with a increased risk of suffering a period of hypoxic–ischaemic encephalopathy and subsequently developing epilepsy [22,23]. …”
mentioning
confidence: 99%